Bi/Multilingualism and Language Shift in Chhantyal - Gautam, Bhim Lal; Adhikari, Manju (Nepalese Linguistics, 2023)
This paper outlines various aspects of bi/multilingualism and language shift in Chhantyal, a minority language community in Nepal. The main objective is to find the domains of language use and the causes of language shift among the migrated Chhantyal in Kathmandu valley. This research is based on mixed methodology of socio-ethnographic survey data where the data were collected with the help of survey questionnaire, key informants interviews (KIIs) and informal discussions and narratives with Chhantyal people based on Gautam (2021).The findings indicate that there is continuous shifts towards Nepali, English and Hindi languages among the speakers influenced by market multilingualism, globalization, migration, travel and tourism.